The structure of the American economy - Eric O'N. Fisher; Kathryn G. Marshall (Center for Economic Studies and ifo Institute (CESifo), 2008)
We explore the relationship between input-output accounts and the national revenue function. The generalized inverse of an economy's technology matrix carries information relating changes in endowments with changes in outputs; its transpose relates output prices and factor prices. Our primary theoretical contribution is to derive an economy's revenue function for an arbitrary Leontief technology. Our main empirical contribution is to compute the national revenue function for the American economy in 2003 and to describe its properties. We implement our ideas using two different models: one where all factors are mobile and another with capital specific to each sector in the economy.
Keywords: E01; D57; O47; 330; Gesamtwirtschaftliche Produktion; Input-Output; Gesamtwirtschaftliches Angebot; Produktionsstruktur; USA